Peningkatan Literasi Membaca Melalui Kolaborasi Guru, Orang Tua, dan Siswa di SD TPI Janji Rantauprapat - munthe, ibnu rasyid; Sari, Novi Fitriandika; Rambe, Bhakti Helvi; Ritonga, Irna Alfaini; Aritonang, Yuliana Br; Fauziah, Ridha (Penerbit Widina, Widina Media Utama, 2024)
This community service program was implemented at TPI Janji Private Elementary School in Labuhanbatu Regency, which has limited access to quality reading materials. Low reading interest and literacy skills among students are primary concerns, as these issues may impact their comprehension, critical thinking, and communication abilities. The program aims to improve students' reading interest and literacy skills through collaboration between teachers, parents, and librarians. The program utilized a participatory approach, with activities such as a mobile library providing quality reading materials. Teachers served as literacy facilitators, while parents were encouraged to create a literacy-rich environment at home. The program demonstrated a significant increase in students' reading interest and literacy skills. The percentage of students reading at least one book per week rose from 15% to 55%. Skills in reading comprehension, speaking, and writing also improved, with an average increase of 40%. This program effectively fostered a literacy culture in the elementary school, particularly in areas with limited access to reading materials. The participatory approach, engaging various stakeholders, yielded positive outcomes and is expected to serve as a sustainable literacy model for other schools.ABSTRAKProgram pengabdian masyarakat ini dilaksanakan di SD Swasta TPI Janji, Kabupaten Labuhanbatu, yang memiliki akses terbatas terhadap bahan bacaan berkualitas. Rendahnya minat baca dan keterampilan literasi siswa menjadi perhatian utama karena berpotensi memengaruhi pemahaman, berpikir kritis, dan kemampuan komunikasi mereka. Program ini bertujuan untuk meningkatkan minat baca dan keterampilan literasi siswa melalui kolaborasi antara guru, orang tua, dan pustakawan. Program menggunakan pendekatan partisipatif dengan kegiatan seperti penggunaan perpustakaan keliling yang menyediakan bahan bacaan berkualitas. Guru berperan sebagai fasilitator literasi, sementara orang tua didorong untuk membangun lingkungan literasi di rumah. Hasil menunjukkan adanya peningkatan signifikan dalam minat baca dan keterampilan literasi siswa. Persentase siswa yang membaca setidaknya satu buku per minggu meningkat dari 15% menjadi 55%. Keterampilan memahami bacaan, berbicara, dan menulis juga mengalami kenaikan rata-rata sebesar 40%. Program ini efektif dalam membangun budaya literasi di sekolah dasar, khususnya di daerah dengan akses bahan bacaan terbatas. Pendekatan partisipatif yang melibatkan berbagai pihak memberikan hasil yang positif dan diharapkan dapat menjadi model literasi berkelanjutan di sekolah-sekolah lain.